2019
DOI: 10.1002/cctc.201900985
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Local Temperature Mapping in Microscopy Nano‐Reactors with Luminescence Thermometry

Abstract: In situ and operando experiments play a crucial role in understanding the mechanisms behind catalytic processes. In these experiments it is important to have precise control over pressure and temperature. In this work, we use luminescence thermometry to map the temperature distribution in a 300 μm microelectromechanical system nano‐reactor with a resolution of ca. 10 μm. These measurements showed a temperature gradient between the center and edge of the heater of ca. 200 °C (at Tset=600 °C) in vacuum and, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
(73 reference statements)
0
52
0
Order By: Relevance
“…Temperature is an important control parameter that governs, e.g., the rate of chemical reactions, but also the optimum working efficiency of electronic devices or dynamics and viability of biological systems. As such, non-invasive, sensitive and remote temperature measurement techniques with the capability to spatially resolve temperature variations down to the micrometer range are becoming increasingly relevant [1][2][3][4][5][6][7]. Physiological temperature sensing is especially demanding in that regard as it even requires to accurately distinguish temperature fluctuations below 1 K. Luminescence nanothermometry is an appealing and rapidly emerging technique that meets those requirements and constantly improves [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is an important control parameter that governs, e.g., the rate of chemical reactions, but also the optimum working efficiency of electronic devices or dynamics and viability of biological systems. As such, non-invasive, sensitive and remote temperature measurement techniques with the capability to spatially resolve temperature variations down to the micrometer range are becoming increasingly relevant [1][2][3][4][5][6][7]. Physiological temperature sensing is especially demanding in that regard as it even requires to accurately distinguish temperature fluctuations below 1 K. Luminescence nanothermometry is an appealing and rapidly emerging technique that meets those requirements and constantly improves [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pérez et al. reported a newly‐designed micro‐heating system with ultra temporal‐stability, which kept the heating sample at constant z‐position (no bulging) up to 700 °C and allowed EDX acquisition in the TEM up to 1000 °C …”
Section: Construction Of In‐situ Temmentioning
confidence: 99%
“…[48][49][50] Recently, Pérez et al reported a newly-designed micro-heating system with ultra temporal-stability, which kept the heating sample at constant z-position (no bulging) up to 700°C and allowed EDX acquisition in the TEM up to 1000°C. [16,51] With the help of precision machining technology and MEMS technology, a special holder equipped with a nanoreactor can be manufactured for in-situ TEM study, which allows gases to be introduced and sealed within the reactor (illustrated in Figure 2c). The nanoreactor was assembled by two (top and bottom) chips with transparent SiN x membranes as windows.…”
Section: Specimen Holdermentioning
confidence: 99%
“…Already various optical methods, such as Raman scattering, thermography, thermal reflection and luminescence have been investigated for use in new types of thermometers [8] . Among these techniques, luminescence‐based thermometry is proving to be a very promising alternative for measuring temperature and has shown excellent results in the first studies on in situ luminescence thermometry during catalytic reactions reported by Meijerink and Weckhuysen [1, 2, 9–12] . Band shape luminescence thermometry is a ratiometric spectroscopic technique, which can be employed to accurately monitor temperature non‐invasively [3] .…”
Section: Introductionmentioning
confidence: 99%